Baños y letrinas en el mundo romano: el caso del "balneum" de la "domus" 1 del barrio de las termas de "Bilbilis" - Sáenz Preciado, J. Carlos; Martín-Bueno, Manuel, 1946-; Reklaityte, Ieva; Uribe Agudo, Paula (2007)
El objetivo de este trabajo es analizar una de las domus del Municipium Augustam Bilbilis (Calatayud, Zaragoza), denominada como Domus del Balneum o Domus 1, excavada durante las campañas arqueológicas de 1997-1999. En esta vivienda, datada en el s. I d. C. se descubrió una pequeña instalación termal, atípica por su ubicación y configuración arquitectónica, provista de hipocaustum, bañera y letrina. La disposición de este elemento dentro de la vivienda respondía a la necesidad del patronus de reafirmar su condición social y económica a través de estos símbolos de ostentación, más cuando en su proximidad, al otro lado de la calle, se ubicaba una de las termas de la ciudad. De este modo, presentamos el análisis de un tema oscuro en la producción científica como son las instalaciones sanitarias, especialmente las letrinas, ubicadas en el contexto de los yacimientos hispanos, así como alguno de sus paralelos en otras provincias romanas.
The aim of this article is to expose a singular Roman domus of Bilbilis (Calatayud, Zaragoza), the so-called Domus del Balneum where there was a private sanitary system found. The existence of such a balneum results curious as its equipment would have been fairly expensive and in fact quite unnecessary because of the close proximity of the public baths. This balneum built approximately in the 1st century A. D. might have been associated to a wealthy citizen; in that case such an emblematic space would have allowed him to reaffirm his social and economic status. The balneum of Bilbilis was composed of a latrine and a bath tube. Misfortunately, almost nothing can be said about the latrine as apart of a hole in the pavement we don't have any more evidence. The dimensions of the rectangular shaped bath tube were 1.8 x 1.2 m and it was made of adobe and masonry with its proper hipocaustum. The water was warmed immersing previously heated up iron refuse. Analysing the emplacement and the execution of the balneum we must remark that the edges of the floor were sealed off with a curve layer to prevent leakages and a gap of a bronze drain pipe that it would seem evacuated the spilt water out of the house. Until now it hasn't been possible to find out whether this pipe was connected to a sewer of the public baths. We suggest that the functioning of the balneum implied the permanent existence of offensive smells and the abundance of flies. This statement could be proved observing the installation of the recipient in order to collect the waste water in the part of hipocaustum at the permanent exposure of heat. Although very little is known about sanitary conditions in the cities of Hispania, a growing body of archaeological evidence all over the Roman Empire reveals drainage systems and private sanitary installations of a relatively sophisticated kind.
Keywords: Civilización romana; Baño